2013
DOI: 10.1016/j.eururo.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Illness Uncertainty and Quality of Life of Patients with Small Renal Tumors Undergoing Watchful Waiting: A 2-year Prospective Study

Abstract: Background Few studies have examined factors associated with the quality of life (QOL) of patients with renal tumors. Illness uncertainty may influence QOL. Objective To prospectively examine the influence of uncertainty on general and cancer-specific QOL and distress in patients undergoing watchful waiting (WW) for a renal mass. Design, setting, and participants In 2006–2010, 264 patients were enrolled in a prospective WW registry. The decision for WW was based on patient, tumor, and renal function charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 24 publications
3
40
0
1
Order By: Relevance
“…Uncertainty regarding a cancer diagnosis can influence perception, such as QoL and expectations . Among patients with RCC undergoing watchful waiting, illness uncertainty (as measured by the Mishel Uncertainty in Illness Scale) was negatively associated with general QoL, cancer‐specific QoL and distress . Our results support the idea that reducing uncertainty regarding diagnosis increases QoL.…”
Section: Discussionsupporting
confidence: 75%
“…Uncertainty regarding a cancer diagnosis can influence perception, such as QoL and expectations . Among patients with RCC undergoing watchful waiting, illness uncertainty (as measured by the Mishel Uncertainty in Illness Scale) was negatively associated with general QoL, cancer‐specific QoL and distress . Our results support the idea that reducing uncertainty regarding diagnosis increases QoL.…”
Section: Discussionsupporting
confidence: 75%
“…Although this study was conducted in Iran, results share some similarity to those found by qualitative studies in other societies. 18,25,27 Both ''Complexity of Cancer'' and ''Confusion About Cancer'' reflect uncertainty in Mishel's themes in studies by others. 25,33 For example, Boyland and Davis 24 reported a theme called ''undergoing multiple investigations,'' in which patients reported complexity in regard to undergoing multiple tests in search of a cancer diagnosis.…”
Section: N Discussionmentioning
confidence: 93%
“…This gap in practice could explain these high levels of ambiguity and unpredictability. The future manifestations of many illnesses have serious effects on children's health and may impact their physical, cognitive, social and emotional development . Reflecting on this, it seems important that all healthcare professionals should endeavour to enhance and develop the care provided for children and their parents to include further information about this aspect of their child's health problem.…”
Section: Discussionmentioning
confidence: 99%